Simultaneous determination of almonertinib and its active metabolite HAS-719 in human plasma by LC-MS/MS: Evaluation of pharmacokinetic interactions - Liu, Lu; Yang, Le; Li, Wei; Chen, Xiaoyan (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2022)
•A LC-MS/MS method for the quantification of almonertinib/HAS-719 in DDI studies.•Acceptable wide linear range and mutual interference of analytes.•The pharmacokinetics evaluation of almonertinib in healthy subjects.•Significant effects of itraconazole and rifampicin on the pharmacokinetics of almonertinib/HAS-719. The combination of two or more drugs in a clinical setting has an impact in pharmacokinetics, drug efficacy and safety, and the study of these interactions has attracted considerable attention over the last years. In the present study, we have developed a LC-MS/MS method for the sensitive and reliable quantification of almonertinib and its active metabolite HAS-719. Further, we investigated the effects of their pharmacokinetics in humans by using modulators of CYP3A, an almonertinib-metabolizing enzyme. Analytes were extracted from plasma samples via acetonitrile-induced protein precipitation and separated on a BEH C18 column using ammonium acetate with formic acid and acetonitrile as the mobile phase. Electrospray ionization in positive ion mode and multiple reaction monitoring were used to monitor the ion transitions at m/z 526 → 411 and 512 → 423. Validation was performed in the range 0.500 to 500 ng/mL for both the analytes of interest according to the guidelines of the U.S. Food and Drug Administration and European Medicines Agency, sufficient to account for variations in plasma concentrations caused by the presence of CYP3A modulators. The selectivity, precision, accuracy, recovery and matrix effect of this method were all within acceptable limits of bioanalytics. The interference of CYP3A modulators itraconazole and rifampicin with the analytes, and the mutual interference between the analytes were also investigated producing acceptable results. The method herein described was successfully applied for the pharmacokinetics evaluation of almonertinib in healthy subjects exposed to a single dose of almonertinib (110 mg), with or without itraconazole or rifampicin.